The role of annuity markets in financing retirement - Brown, Jeffrey R. (Jeffrey Robert), 1968- (MIT Press, 2001)
Annuity insurance products help protect retirees against outliving their incomes. Dramatic advances in life expectancy mean that today's retirees must plan on living into their eighties, their nineties, and even beyond. Longer life expectancies are the symbol of a prosperous society, but this progress also means that some retirees will need to plan conservatively and cut back substantially on their living standards or risk living so long that they exhaust their resources. This book examines the role that life annuities can play in helping people protect themselves against such outcomes. A life annuity is an insurance product that pays out a periodic amount for as long as the annuitant is alive, in exchange for a premium. The book begins with a history of life annuity markets during the twentieth century in the United States and elsewhere. It then explores recent trends in annuity pricing and money's worth, as well as the economic value generated for purchasers of these products. The book explains the potential importance of inflation-protected annuities and stock-market-linked variable annuities in providing more complete retirement security. The concluding chapters examine life annuities in various institutional settings and the tax treatment of annuity products.